2010
DOI: 10.1007/s00421-010-1766-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effect of aging on submaximal leg exercise hemodynamics in middle-aged and older adults

Abstract: The purpose of the study was to examine predictors of the leg hemodynamic response to exercise in middle- and older-aged men and women. Femoral artery blood flow (FBF), mean arterial pressure (MAP), and femoral vascular conductance (FVC, calculated as the quotient of FBF and MAP) were measured at rest and during 5 min of single knee-extensor exercise at ~10 W workload in healthy men (n = 31) and women (n = 32) (age 40-72 years). Age, menopausal status, maximal quadriceps strength, blood lipids, vitamin D level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…Finally, our results suggest that the improvement in exercise hemodynamics are independent of LDL reduction adding improved exercise leg hemodynamics to the potential pleiotropic effects of statins. Notably, the ~20–25% increase in leg exercise hyperemia observed in the current study is equivalent to the magnitude of impairment observed in older adults or patients with Type II diabetes and heart failure (4;5;16). Therefore, statins may also be an effective therapy for treating blunted exercise hyperemia.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Finally, our results suggest that the improvement in exercise hemodynamics are independent of LDL reduction adding improved exercise leg hemodynamics to the potential pleiotropic effects of statins. Notably, the ~20–25% increase in leg exercise hyperemia observed in the current study is equivalent to the magnitude of impairment observed in older adults or patients with Type II diabetes and heart failure (4;5;16). Therefore, statins may also be an effective therapy for treating blunted exercise hyperemia.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, on the 3 rd pre-study and 2 nd post-study visits, subjects performed one, 5 minute bout of single-knee extension exercise at a cadence of 40 kicks/minute using the Biodex System 3 as previously described (16). Single knee extensor exercise is not limited by cardiac output and elicits less excitation of the sympathetic nervous system than two-legged exercise, and is thus effective for examining the leg vasodilatory response to exercise independent of central limitations and alterations (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies on aging and active leg blood flow in women have been limited to two age groups: young (20–30 years) and old (60–75 years) (Parker et al 2008 a , 2008 b ; Proctor et al 2003 a ). Parker et al (2011) recently provided evidence that leg blood flow and conductance during knee extensor exercise are influenced by menopausal status, independent of age, in middle-aged and older women. However, the exercise protocol used was limited to a single, light work intensity (~10 W), and no perimenopausal women were included and reproductive hormones were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas leg hyperemia and vascular conductance are well preserved during submaximal exercise in older men that are neither endurance trained nor overly sedentary (Parker et al 2008 a ; Proctor et al 2003 b ), leg blood flow and vascular conductance responses during submaximal two-legged cycling (Proctor et al 2003 a ) and single-leg knee extensor exercise (Parker et al 2008 a , 2008 b ) are attenuated in older versus younger women. Although the mechanisms underlying these age-associated reductions in exercise hyperemia and vasodilation in women are unknown, evidence suggests that they may be related to menopausal status (Parker et al 2011). …”
Section: Introductionmentioning
confidence: 99%